1999
DOI: 10.1038/sj.cgt.7700063
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon α2a synergistically enhances ganciclovir-mediated tumor cell killing in the herpes simplex virus thymidine kinase system

Abstract: The herpes simplex virus thymidine kinase (HSV-TK) gene is being developed in the treatment of many different types of tumors. The HSV-TK gene sensitizes tumor cells to the antiviral drug ganciclovir (GCV) and mediates the bystander effect in which unmodified tumor cells are killed as well. Although this approach has shown a significant antitumor effect, the need to potentiate this therapy exists. The results of this study indicate that recombinant interferon ␣2a (IFN␣2a) acts synergistically with GCV to kill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…27 In this study, the bystander effects were more potent in vitro, in which one tumor cell expressing the HSV-TK gene destroyed approximately two neighboring cells, compared with in vivo, in which each of two transduced cells killed only one bystander cell. Taken together with the findings on T/C ratios, this makes immunological mechanisms in the mediation of the bystander-killing effect less likely.…”
Section: Discussionmentioning
confidence: 65%
“…27 In this study, the bystander effects were more potent in vitro, in which one tumor cell expressing the HSV-TK gene destroyed approximately two neighboring cells, compared with in vivo, in which each of two transduced cells killed only one bystander cell. Taken together with the findings on T/C ratios, this makes immunological mechanisms in the mediation of the bystander-killing effect less likely.…”
Section: Discussionmentioning
confidence: 65%
“…Our previous studies showed that although IFN significantly increased the toxicity of GCV, it did not enhance the incorporation of GCV into cellular DNA, suggesting that there was no correlation between the amount incorporated and cell killing. 10 Our present studies showed that after removal of GCV from the extracellular medium, no significant amounts of GCV were excised, even in the absence of IFN exposure, suggesting that the repair enzymes did not recognize it as an illegitimate base, and DNA synthesis was not immediately stopped by its presence.…”
mentioning
confidence: 53%
“…10 These assays have been validated for this system. Both types of assays were conducted for all studies related to toxicity and were confirmatory.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…Some new strategies have been proposed to enhance the antitumor effects of suicide gene therapy, that is, by induction of immune responses to tumor cells via coexpression of cytokine and chemokine genes. Recent studies have demonstrated that codelivery strategies employing IL-2 and HSV-tk, 31 IL-2, GM-CSF and HSV-tk, 32 IL-12 and HSV-tk, 33 IL-4 and HSV-tk, 34 TNF-a and HSV-tk, 35 as well as IFN-a2a and HSV-tk 36 are relatively effective compared to treatment with the suicide gene alone.…”
Section: Discussionmentioning
confidence: 99%